Operational Research-Driven Social Media Strategies for Sustainable SMEs Growth in Thailand’s Technology Sector - David Kiatsangsilp; Sumaman Pankham (Decision Making: Applications in Management and Engineering, 2025)
Small and medium-sized enterprises (SMEs) operating within the computer technology sector constitute a significant contributor to Thailand’s digital economic advancement. This study employs the principles of operational research to both construct and validate a Structural Equation Model (SEM), with the objective of identifying sustainable growth trajectories for technology-based SMEs in the country. Expert consensus was gathered from a panel of 20 professionals representing academia, entrepreneurial practice, and public policy. A mixed-methods research design was adopted, wherein the qualitative phase utilised the e-Fuzzy Delphi method. For the quantitative phase, SEM was applied to data obtained through a structured online survey completed by 848 SMEs entrepreneurs. The resulting model integrates existing empirical findings across behavioural and technological domains. It focuses on how factors such as social media use, service quality, perceived behavioural control, and attitude, along with the influence of subjective norms, contribute to predicting user satisfaction, usage intentions, actual usage behaviour, and ultimately, sustainable enterprise growth. Findings highlight the pivotal influence of social expectations in shaping both the intention to use and the corresponding user behaviour, which are essential to achieving sustained development. This research exemplifies the synergy between operational research methodologies and strategic decision-making processes within a data-informed modelling framework. It further identifies key behavioural drivers that provide policymakers with practical recommendations for advancing digital sustainability in Thailand’s SMEs landscape